A Tale of Two Tournaments - Chad Carlson (University of Kansas Libraries, 2012)
The purpose of this article is to explore the relationship between the National Invitational Tournament (NIT) and National Collegiate Athletic Association (NCAA). To do so, the author explores the Red Cross War Benefit Games, which pitted the champions of the two tournaments against one another, with the proceeds benefiting the Red Cross. These contests represented the only times the two tournaments or their teams interacted. The author explores the Games' significance and the manner in which they helped propel the NCAA men's basketball tournament to preeminent status.